2024
DOI: 10.3389/fphar.2024.1337749
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the multifaceted potential of (R)-ketamine beyond antidepressant applications

Senbing Zhang,
Yanzhu Pu,
Jianning Liu
et al.

Abstract: (R, S)- and (S)-ketamine have made significant progress in the treatment of treatment-resistant depression (TRD) and have become a research focus in recent years. However, they both have risks of psychomimetic effects, dissociative effects, and abuse liability, which limit their clinical use. Recent preclinical and clinical studies have shown that (R)-ketamine has a more efficient and lasting antidepressant effect with fewer side effects compared to (R, S)- and (S)-ketamine. However, a recent small-sample rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…Table 2 shows a list of these ideas along with the rationale from the experimental findings that are discussed in this section. Prior reviews of this area can be found [56,57]. Racemic ketamine has long been known for its anesthetic properties [1] and is currently utilized in the management of pain in some cases where other therapies are not effective [58].…”
Section: Other Potential Therapeutic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows a list of these ideas along with the rationale from the experimental findings that are discussed in this section. Prior reviews of this area can be found [56,57]. Racemic ketamine has long been known for its anesthetic properties [1] and is currently utilized in the management of pain in some cases where other therapies are not effective [58].…”
Section: Other Potential Therapeutic Applicationsmentioning
confidence: 99%
“…Table 2 shows a list of these ideas along with the rationale from the experimental findings that are discussed in this section. Prior reviews of this area can be found [ 56 , 57 ].…”
Section: Other Potential Therapeutic Applicationsmentioning
confidence: 99%